The big book of useless knowledge: 250 of the coolest, weirdest, and most unbelievable facts you won't be taught in school - Borowiec, Brittney G., Dr; Atkinson, Victoria, Dr; Buller, Laura; Haridy, Yara; Goldfield, Anna; Pérez Díaz, Lucía; Allan, Sophie (Physics teacher) (Neon Squid, 2024)
"Heard about the lizard that shoots blood from its eyes? Or the ancient Romans who used pee to clean their clothes? Did you know that going on a roller coaster can cure kidney stones? A team of experts has scoured the world to find the most surprising facts it has to offer."--